Tea consumption and cardiovascular risk and outcomes: mechanistic insights, epidemiological evidence, and clinical implications - Rong Liu; Jialin Li; Yanchun Liang (Frontiers in Cardiovascular Medicine, 2026)
Cardiovascular disease (CVD) remains a leading cause of morbidity and mortality worldwide. Tea contains bioactive compounds with plausible antioxidant, anti-inflammatory, endothelial, metabolic, antithrombotic, and gut microbiota-mediated effects. Observational studies generally associate habitual tea consumption with lower risks of atherosclerotic CVD and mortality, but causal inference remains uncertain because secondary-prevention data are limited, randomized trials focus mainly on surrogate outcomes, and Mendelian randomization has not consistently supported causal cardiovascular effects. Differences in tea composition and patient characteristics provide a rationale for individualized tea-consumption strategies; however, current evidence does not support disease-specific tea selection or a standardized therapeutic dose. Interpretation is further limited by residual confounding, reverse causation, heterogeneous exposure definitions, bioavailability, and safety considerations. Future studies should standardize tea exposure and evaluate clinical cardiovascular endpoints in adequately powered randomized trials to determine whether personalized tea strategies have clinical value.